Do peer attachment, perceived school climate, and parental involvement influence self-awareness in students? - Dwi Nur Rachmah; Nathasya Inneke Putri; Rizkika Rizkika; Saidatul Magfirah; Siti Halimatussa’diah (LPMPP Universitas Negeri Yogyakarta, 2022)
This study was aimed at investigating the effect of peer attachment, parental involvement, and perceived school climate on self-awareness in junior high school students in East Martapura, South Kalimantan Province, Indonesia. The quantitative research method through product moment correlation and multiple linear regression analysis was applied in this study. The sample of the research was the total population of a junior school in East Martapura with significant number of dropout cases. The subject of this study consisted of male and female students in the age of 11 to 17 years old with a family background of traders and farmers as well as a Malay-bajar Islamic culture. The results of the study showed that there was a significant correlation between peer attachment and parental involvement. In contrast, there was no correlation between both factors and perceived school climate. Furthermore, it was also found that there was a significant positive effect of peer attachment, parental involvement, and perceived school climate on students' self-awareness. The results of this study indicated that to foster students’ self-awareness, schools need to establish communication with parents, create a comfortable and effective school climate for teaching and learning processes, as well as facilitate the students to develop peer attachment through extracurricular activities. In addition, schools may also take actions to implement field-based learning and provide career counseling for students to broaden their insights of alternative self-development besides trading and farming.